Reduction of NOx emissions from gas turbine combustor with fuel staging - Mohammad Nazri Mohd.la'afar, (2002)
A two stage lean/lean gas turbine combustor was developed with low NOx characteristics in each stage using small radial swirler of 40mm outlet diameter in the pilot stage. Both flame tubes were arranged in series with the smaller combustor (76mm inside diameter) as the pilot stage and the larger combustor (140mm inside diameter) as the main stage. The pilot stage was fuelled via vane passage fuel injectol; while the main stage was fuelled around the wall of the exit plane of the pilot stage, using wall fuel injectors. Ultra low NOx emissions as low as 15 ppm were obtained when using fuel staging for propane fuel. NOxreduction of 68% was obtained at equivalence ratio of 0.74, when using fuel staging compared to the non-fuel staging tests. This was achieved with small decrease in carbon monoxide emissions and no increase at all in the unburned hydrocarbon emissions at the same equivalence ratio